All through the night : important jobs that get done at night - Faber, Polly (Nosy Crow, an imprint of Candlewick Press, 2022)
"The sky is getting dark. In the city, a little girl is eating her dinner, brushing her teeth, and getting ready for bed. Meanwhile, her mother is putting on her coat and getting ready to go to work. Where is she going and who will she see along the way? As the night goes on, readers will see nurses, cleaners, delivery workers, doctors, police officers, journalists, and many other workers who help keep the city running all through the night."--